Inhibition of Anchorage-Independent Proliferation and G0/G1 Cell-Cycle Regulation in Human Colorectal Carcinoma Cells by 4, 7-Dimethoxy-5-Methyl-l, 3-Benzodioxole Isolated from the Fruiting Body of Antrodia camphorate. (8th June 2011) - Lien, Hsiu-Man; Lin, Hsiao-Wei; Wang, Ying-Jan; Chen, Li-Ching; Yang, Ding-Yah; Lai, Ya-Yun; Ho, Yuan-Soon
Abstract : In this study, 4, 7-dimethoxy-5-methyl-l, 3-benzodioxole (SY-1) was isolated from three different sources of dried fruiting bodies of Antrodia camphorate ( AC ). AC is a medicinal mushroom that grows on the inner heartwood wall of Cinnamomum kanehirai Hay ( Lauraceae ), an endemic species that is used in Chinese medicine for its anti-tumor and immunomodulatory properties. In this study, we demonstrated that SY-1 profoundly decreased the proliferation of human colon cancer cells (COLO 205) through G0/G1 cell-cycle arrest (50–150  μ M) and induction of apoptosis (>150  μ M). Cell-cycle arrest induced by SY-1 was associated with a significant increase in levels of p53, p21/Cip1 and p27/Kip1, and a decrease in cyclins D1, D3 and A. In contrast, SY-1 treatment did not induce significant changes in G0/G1 phase cell-cycle regulatory proteins in normal human colonic epithelial cells (FHC). The cells were cultured in soft agar to evaluate anchorage-independent colony formation, and we found that the number of transformed colonies was significantly reduced in the SY-1-treated COLO 205 cells. These findings demonstrate for the first time that SY-1 inhibits human colon cancer cell proliferation through inhibition of cell growth and anchorage-independent colony formation in soft agar. However, the detailed mechanisms of these processes remain unclear and will require further investigation.